Analyzing Pre-Service Teachers' Needs and Perceptions: Integrating Technology-Enhanced AfL, AaL, and AoL within Differentiated Instruction in Indonesian EFL Contexts - Maknun, Lu'luil; Daniel Ari Widhiatama (Universitas Cokroaminoto Palopo, 2026)
This study analyzed EFL pre-service teachers' target and learning needs for developing an instructional model of technology-based AfL, AaL, and AoL. in the context of differentiated instruction. The approach employed in this research involves a qualitative methodology utilizing questionnaires and interviews as primary data collection instruments. Interviews with nine EFL lecturers and questionnaires distributed to 200 Indonesian EFL pre-service teachers explored their lacks, necessities, wants, roles, settings, and learning activities related to technology-based AfL, AaL, and AoL. The findings revealed that EFL pre-service teachers have diverse needs for technology-driven AfL, AaL, and AoL in differentiated English education. The lack demonstrated that they invest considerable time in preparing instructional materials and assessments, often struggling to select the appropriate technology for effectively implementing AfL, AoL, and AaL. Challenges arise in providing feedback during AfL because there are few strategies to accommodate students with diverse learning styles. The study recommends future research to develop an instructional model of technology-based AfL, AaL, and AoL for EFL pre-service teachers, providing standard guidelines to maximize the EFL teaching-learning process and assessment within the differentiated instruction framework.